WEED CONTROL EFFICACY OF TRIAFAMONE 200 SC IN TRANSPLANTED RICE - B, JYOTHI BASU (The Journal of Research ANGRAU, 2026)
A field investigation conducted during two consecutive cropping seasons (Rabi 2017–18and Kharif 2018–19) at the Agricultural Research Station, Jangamaheswarapuram, AndhraPradesh, India, to evaluate the performance of Triafamone 200 SC in transplanted Rice.”Amongthe various herbicide treatments, Triafamone 200 SC applied at 100 g a.i. ha-¹ at 0-3 days aftertransplanting (DAT) recorded superior weed suppression efficiency in Rabi 2017-18 (68.64%)and in Kharif 2018-19 (60.83%) and also yielded 4967 kg ha-1 in Rabi and 5518 kg ha-1 in Kharif,withperformance comparable to conventional farmer-managed two hand weeding practices, whichproduced 5342 kg ha-1 in Rabi and 5849 kg ha-1 in Kharif. The weed-free treatment recorded themaximum yields (5762 kg ha-1 in Rabi and 6376 kg ha-1 in Kharif), while the weedy check plotsshowed the lowest yields (3066 kg ha-1 in Rabi and 3825 kg ha-1 in Kharif).